Impact of Social Media on Stock Market Volatility of Nepal - Maharjan, Nishchal (Nepalese Journal of Finance, 2025)
This study examines the impact of social media on stock market volatility of Nepal. Stock market volatility is the dependent variables. The selected independent variables are social media activity, market fundamentals, investor sentiment, market liquidity and news coverage. The primary source of data is used to assess the opinions of respondents regarding social media activity, market fundamentals, investor sentiment, market liquidity and news coverage. The study is based on primary data. The primary data were gathered from 106 respondents through questionnaires. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of social media on stock market of Nepal. The study showed a positive impact of social media activity on stock market volatility. It indicates that an increase in social media activity leads to an increase in stock market volatility. Similarly, the study showed a positive impact of market fundamentals on stock market volatility. It indicates that better the market fundamentals, higher would be the stock market volatility. Likewise, the study also revealed a positive impact of investor sentiment on stock market volatility. It indicates that higher investor sentiment leads to increase in stock market volatility. Further, the study observed a positive impact of market liquidity on stock market volatility. It indicates that higher market liquidity leads to increase in stock market volatility. In addition, the study observed a positive impact of news coverage on stock market volatility. It indicates that better coverage leads to increase in stock market volatility.